Melatonin: Manager of psychosomatic and metabolic disorders in polymorbid cardiovascular pathology - Alexander S. Partsernyak; Victoria O. Polyakova; Artem G. Trufanov; Artem G. Trufanov; Dmitriy S. Medvedev; Dina V. Trotsyuk; Kirill Markin; Evgeniy S. Kurasov; Evgeniya V. Kuznetsova; Alexander S. Krasichkov (Frontiers in Neuroscience, 2022)
ObjectivesTo investigate the relationship between changes in circadian patterns of melatonin and clinical manifestations of polymorbid cardiovascular pathology (PCVP) in young men and to analyze the effectiveness of their complex treatment.Materials and methodsWe made the immunohistochemical (IHC) analysis of epiphysis tissues from autopsies of 25 men aged 32–44 with PCVP and metabolic syndrome (MS) who had died as a result of ischemic cardiomyopathy (IC) and 25 persons after the car accident as a control group. Then, 93 young men aged 35–44 with PCVP, metabolic syndrome, and depressive spectrum disorders (DSD) were divided into three groups: (1) standard therapy; (2) standard therapy and psychotherapy sessions; (3) standard therapy in combination with psychotherapeutic and psychophysiological visual and auditory correction sessions. The control group included 24 conditionally healthy male volunteers. Before and after the treatment, we studied the anthropometric status, lipid and carbohydrate metabolism indicators, the level of urinary 6-hydroxymelatonin sulfate, the degree of nocturnal decrease in blood pressure (BP), and the relationship of these indicators with circadian variations of melatonin excretion.ResultsYoung polymorbid patients who died from IC have a lower expression of melatonin type 1 and 2 receptors. All patients with PCVP showed a decrease in the nocturnal melatonin excretion fraction and a correlation with higher severity of depressive (r = −0.72) and anxiety (r = −0.66) symptoms. Reduced values of the 6-hydroxymelatonin sulfate (6-SM) in the 1st (r = 0.45), 2nd (r = 0.39), and 3rd (r = 0.51) groups before treatment was associated with periods of increased BP. The achievement of melatonin excretion reference values and normalization of biochemical parameters of carbohydrate and lipid metabolism, daily BP profile, and psychophysiological state were noted in all three patients’ groups, with a more pronounced effect in group 3.ConclusionLow nocturnal melatonin excretion levels are associated with greater severity of clinical symptoms and a higher risk of death in patients with PCVP. Therefore, comprehensive therapy may be more effective for correcting this disease.